APLIKASI BELAJAR BAHASA KOREA BEBBASIS MULTIMEDIA (Information Technology and Telematics, 2012)
Language is a means for communicating a nation. Various languages ​​in the world, making every country has a different language. Making learning the Korean language media became a writer of ideas to attract interest in learning the Korean language. The introduction of Hangul characters on which to base so you can easily learn the Korean language which the author presented in the form of multimedia-based aid program. By using multimedia development and design stages stroryboard authors make the program easier. The use of adobe flash as the main software program making. Key words: Learning the Korean language, Multimedia, Adobe Flash